FORMATION OF AN ORGANIZATIONAL AND ECONOMIC MECHANISM FOR DEVELOPING THE ECONOMIC POTENTIAL OF AN ENTERPRISE - VYSHNIUK, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the theoretical and methodological foundations of forming strategic decisions in managing the process of developing the economic potential of an enterprise, which serves as a determining factor for ensuring its sustainable growth and competitive resilience in the modern economic environment. It emphasizes that the development of economic potential should be considered not merely as an increase in available resources but as a qualitative transformation of the enterprise’s capabilities in response to internal and external challenges. The study systematizes the principles of building an organizational and economic mechanism that integrates structural, informational, and managerial subsystems, providing coordinated interaction among the key elements of the enterprise’s management system. This mechanism ensures the dynamic development of economic potential through the combination of strategic, tactical, and operational management levels. Special attention is devoted to the methodological aspects of assessing the enterprise’s economic potential, which include the evaluation of competitiveness, resource efficiency, innovative capabilities, and adaptability to environmental changes. The article proposes a conceptual model of strategic decision-making, which encompasses comprehensive and element-wise assessment of potential, identification of development goals, selection of criteria and influencing factors, and implementation of feedback-based control mechanisms. The results highlight that the development of an enterprise’s economic potential is a continuous and cyclical process requiring constant monitoring, analytical support, and flexible managerial tools. The research outcomes can be practically applied in the design and implementation of strategic management systems aimed at strengthening enterprise adaptability, increasing the efficiency of resource utilization, and fostering innovative development.
Keywords: strategic decisions; economic potential; development management; organizational and economic mechanism; strategic planning; competitiveness